Aqueous resin dispersion, its method of manufacture and ink containing said dispersion
An aqueous resin dispersion containing urethane and acrylic polymers in the same particles, with specific structural units and glass transition temperatures, addresses the challenges of adhesion and gloss on low surface tension substrates, achieving low viscosity and excellent coating properties for water-based inks.
Patent Information
- Application Number
- JP2023506972
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-16
- Filing Date
- 2022-03-04
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2042-03-04
AI Technical Summary
Existing aqueous resin dispersions face challenges in achieving good adhesion and gloss on low surface tension substrates like polypropylene, and they often result in high viscosity and poor coating performance when used in water-based inks.
The development of an aqueous resin dispersion containing urethane polymer A and acrylic polymer B in the same particles, where the acrylic polymer B has a structural unit derived from a radical polymerizable monomer with an alicyclic skeleton, resulting in a glass transition temperature of -60°C or more and less than 5°C, which improves adhesion and gloss on various plastic film substrates.
This solution enables the production of a coating film with low viscosity and excellent coating properties, providing good adhesion and gloss to various plastic film substrates, and is suitable for use as a raw material in water-based inks.
Smart Images

Figure 0007663115000001 
Figure 0007663115000002 
Figure 0007663115000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous resin dispersion and an ink containing said dispersion. This application claims priority based on Japanese Patent Application No. 2021-042708, filed on March 16, 2021, the contents of which are incorporated herein by reference. [Background technology]
[0002] Aqueous resin dispersions for aqueous coating materials are widely used in a variety of applications because they have excellent mechanical properties and chemical resistance, and can be molded easily at low cost. These resins also have excellent recyclability, and their applications are expanding further in light of recent global environmental issues. However, it is generally considered difficult to adhere to substrates such as polypropylene, which has low surface tension and is difficult to adhere to. As an aqueous resin dispersion for aqueous coating materials, for example, Patent Document 1 describes a method of using an aqueous emulsion of an acrylic-urethane block copolymer having a pendant nonionic hydrophilic group and a pendant anionic hydrophilic group on the side chain of the urethane block that crosslinks the acrylic block. Also, Patent Document 2 describes a method of using an acrylic-urethane composite resin emulsion in which an ethylenically unsaturated monomer is reacted with a urethane urea resin containing mercapto groups at both ends.
[0003] The method described in Patent Document 1 has good film-forming properties, but has the problem that it is difficult to impart adhesion to poorly adherent substrates with low surface tension, such as polypropylene substrates, because pendant nonionic hydrophilic groups and pendant anionic hydrophilic groups are introduced into the side chains of the urethane block in order to impart film-forming properties.
[0004] In addition, the method described in Patent Document 2 has excellent ink pigment dispersibility and adhesion to non-polar film substrates, but has the problem that the ink has acidic groups in the acrylic blocks, and therefore thickens when exposed to low-molecular-weight alcohols that are commonly used as dilution solvents for aqueous inks, etc., resulting in poor coatability as an aqueous ink. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-057451 A [Patent Document 2] JP 2017-002222 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide an aqueous resin dispersion which, when used as a raw material for an aqueous ink, has low viscosity and excellent coatability, and can give a coating film having good adhesion to various plastic film substrates and good gloss, and an ink containing the dispersion. [Means for solving the problem]
[0007] That is, the present invention relates to the following [1] to
[32] . [1] An aqueous resin dispersion comprising a urethane polymer A and an acrylic polymer B contained in the same particle, the acrylic polymer B having a constitutional unit derived from a radically polymerizable monomer having an alicyclic skeleton, and the acrylic polymer B having a glass transition temperature of -60°C or higher and lower than 5°C. [2] The aqueous resin dispersion according to [1], wherein the acrylic polymer B contains structural units derived from a radically polymerizable monomer having an alicyclic skeleton in an amount of 5 mass% or more relative to the total mass of structural units constituting the acrylic polymer B. [3] The aqueous resin dispersion according to [1] or [2], wherein the glass transition temperature of the acrylic polymer B is -40°C or higher and -2°C or lower. [4] The aqueous resin dispersion according to any one of [1] to [3], wherein the acrylic polymer B has a glass transition temperature of −40° C. or higher and −6° C. or lower. [5] The aqueous resin dispersion according to any one of [1] to [4], wherein the aqueous resin dispersion has a hydrodynamic average particle diameter of 120 nm or less as measured by a dynamic light scattering method. [6] The aqueous resin dispersion according to any one of [1] to [5], wherein the solid content of the aqueous resin dispersion is 35 mass % or more based on the total mass of the aqueous resin dispersion. [7] The aqueous resin dispersion according to any one of [1] to [6], wherein the acrylic polymer B contains a constituent unit derived from a radically polymerizable monomer having an alicyclic skeleton in an amount of preferably 5% by mass or more and 95% by mass or less, more preferably 10% by mass or more and 90% by mass or less, and even more preferably 30% by mass or more and 85% by mass or less, based on the total mass of the constituent units constituting the acrylic polymer B. [8] The aqueous resin dispersion according to any one of [1] to [7], wherein the radical polymerizable monomer having an alicyclic skeleton in the acrylic polymer B is preferably at least one selected from the group consisting of cyclohexyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and 4-t-butylcyclohexyl (meth)acrylate, more preferably at least one selected from the group consisting of cyclohexyl (meth)acrylate and isobornyl (meth)acrylate. [9] The aqueous resin dispersion according to any one of [1] to [8], wherein the acrylic polymer B contains a constituent unit derived from another vinyl-based monomer d copolymerizable with the radically polymerizable monomer having an alicyclic skeleton, and the content of the constituent unit derived from the other vinyl-based monomer d is more preferably 10% by mass or more and 90% by mass or less, and even more preferably 25% by mass or more and 70% by mass or less.
[10] The other vinyl monomer d is preferably at least one selected from the group consisting of alkyl(meth)acrylates having an alkyl group with 1 to 18 carbon atoms, hydroxyalkyl(meth)acrylates, glycol di(meth)acrylates, alkylamino(meth)acrylates, monomers having an acid group, dimethylaminoethyl(meth)acrylate methyl chloride salts, allyl(meth)acrylates, trimethylolpropane tri(meth)acrylates, glycidyl(meth)acrylates, styrene, vinyl acetate, vinyl propionate, and (meth)acrylonitrile; methyl(meth)acrylate, ethyl(meth)acrylate The aqueous resin dispersion according to any one of [1] to [9], wherein the acrylate is at least one selected from the group consisting of n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate, and further preferably at least one selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.
[11] The aqueous resin dispersion according to any one of [1] to
[10] , wherein the average particle size of the urethane polymer A measured by photon correlation spectroscopy is preferably 30 to 100 nm, and more preferably 40 to 80 nm.
[12] The aqueous resin dispersion according to any one of [1] to
[11] , wherein the viscosity of the urethane polymer A at 20° C. measured in accordance with DIN 53019 is preferably from 10 to 50 mPa s, and more preferably from 20 to 40 mPa s.
[13] The aqueous resin dispersion according to any one of [1] to
[12] , wherein the content of the acrylic polymer B relative to the total mass of the urethane polymer A and the acrylic polymer B is preferably from 10 to 80 mass%, more preferably from 20 to 50 mass%.
[14] The aqueous resin dispersion according to any one of [1] to
[13] , wherein the content of the acrylic polymer B relative to the total mass of the urethane polymer A and the acrylic polymer B is preferably from 20 to 90 mass%, and more preferably from 50 to 80 mass%.
[15] The aqueous resin dispersion according to any one of [1] to
[14] , wherein the solid content of the aqueous resin dispersion is preferably from 30% by mass to 60% by mass, and more preferably from 35% by mass to 50% by mass, relative to the total mass of the aqueous resin dispersion.
[16] The aqueous resin dispersion according to any one of [1] to
[15] , wherein the aqueous resin dispersion has a hydrodynamic average particle size measured by a dynamic light scattering method of preferably 30 to 150 nm, more preferably 40 to 100 nm.
[17] The aqueous resin dispersion according to any one of [1] to
[16] , wherein an ink containing the aqueous resin dispersion is prepared, and the viscosity of the ink is measured at 23°C using a Zahn cup No. 3 (manufactured by Tester Sangyo Co., Ltd.). The Zahn cup passing time is preferably less than 10 seconds, more preferably less than 10 seconds and 3 seconds or more, and even more preferably 9.5 seconds or less and 5.0 seconds or more.
[18] The aqueous resin dispersion according to any one of [1] to
[17] , wherein an ink containing the aqueous resin dispersion is prepared, the ink is printed on a resin film to form an ink coating film, and the ink is dried under drying conditions of 25°C for 1 day to form an ink coating film having a thickness of 1 to 2 µm after drying. The gloss (60°) of the ink coating film is preferably 10.5 or more and 20.0 or less, more preferably 9.0 or more and 18.0 or less, as measured using a variable angle gloss meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name: GLOSS METER VG7000).
[19] The aqueous resin dispersion according to any one of [1] to
[18] , wherein an ink containing the aqueous resin dispersion is prepared, the ink is printed on a resin film to form an ink coating, and the ink is dried under drying conditions of 25°C for 1 day to form an ink coating having a thickness of 1 to 2 µm after drying. Cellophane tape (manufactured by Nichiban Co., Ltd., product name: CT405AP-12) is attached to the ink coating, and a peeling test is performed in the vertical direction to measure adhesion to the substrate. The ink remaining on the substrate is preferably 15 area % or more and 100 area % or less, more preferably 20 area % to 100 area %, and even more preferably 30 area % to 99 area %.
[20] The SP value of the acrylic polymer B calculated by the fedors' estimation formula from the feed ratio of the raw material monomers is 9.5 to 11.0 (cal / cm 3 ) 1 / 2 is preferable, and 9.7 to 10.1 (cal / cm 3 ) 1 / 2 The aqueous resin dispersion according to any one of [1] to
[19] , wherein:
[21] The aqueous resin dispersion according to any one of [1] to
[20] , wherein the glass transition temperature of the acrylic polymer B is preferably −40° C. or more and −2° C. or less, more preferably −40° C. or more and less than −6° C., and even more preferably −40° C. or more and less than −10° C.
[22] The aqueous resin dispersion according to any one of [1] to
[21] , wherein the mass ratio of the urethane polymer A to the acrylic polymer B is preferably from 20:80 to 90:10, and more preferably from 40:60 to 70:30.
[23] The aqueous resin dispersion according to any one of [1] to
[22] , wherein the particles are core-shell particles having a core layer and a shell layer, the core layer containing the urethane polymer A and the shell layer containing the acrylic polymer.
[24] The method for producing the aqueous resin dispersion according to any one of [1] to
[23] , wherein the acrylic polymer B is produced by polymerization using 0.35 mass% or less of a radical polymerization initiator based on the total amount of radically polymerizable monomers for constituting the acrylic polymer B.
[25] The method for producing the aqueous resin dispersion according to any one of [1] to
[23] , comprising seed polymerizing a radical polymerizable monomer for constituting the acrylic polymer B using the urethane polymer A as a seed to produce the particles.
[26] The method for producing an aqueous resin dispersion according to
[24] or
[25] , wherein the polymerization temperature is preferably 10 to 90°C, and more preferably 30 to 70°C.
[27] The method for producing the aqueous resin dispersion according to any one of
[24] to
[26] , wherein the amount of the radical polymerization initiator used in the polymerization is preferably 0.01 to 5 mass%, more preferably 0.05 to 2 mass%, and even more preferably 0.10 to 1 mass%, based on the total amount of the radically polymerizable monomers for constituting the acrylic polymer B.
[28] An ink containing the aqueous resin dispersion according to any one of [1] to
[23] .
[29] The ink according to
[28] , further comprising a pigment paste.
[30] Use of the aqueous resin dispersion according to any one of [1] to
[23] for producing an ink.
[31] The use according to
[30] , wherein the ink contains the aqueous resin dispersion according to any one of [1] to
[23] .
[32] The use according to
[30] or
[31] , wherein the ink contains a pigment paste. Effect of the Invention
[0008] According to the present invention, it is possible to provide an aqueous resin dispersion which, when used as a raw material for an aqueous ink, has low viscosity and excellent coatability, and can give a coating film having good adhesion to various plastic film substrates and good gloss, and an ink containing the dispersion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In the present invention, "(meth)acrylate" is a general term for acrylate and methacrylate, and "(meth)acrylic acid" is a general term for acrylic acid and methacrylic acid. The term "structural unit derived from a monomer" refers to a structural unit derived from a monomer that constitutes a polymer. "Solid content" refers to non-volatile components at 0.1 MPa and 105°C.
[0010] The aqueous resin dispersion of the present invention contains, in the same particle, a urethane polymer A and an acrylic polymer B. The aqueous resin dispersion may further contain components such as additives in addition to the polymer A and the polymer B.
[0011] <Urethane polymer A> The urethane polymer A is a polymer having a urethane bond obtained by reacting a polyol a with a polyisocyanate b.
[0012] The urethane polymer A promotes the film formation of the aqueous coating composition and imparts adhesion to polar substrates such as polyethylene terephthalate to the resulting coating film. The content of the acrylic polymer B relative to the total mass of the urethane polymer A and the acrylic polymer B is preferably 10 to 80% by mass, more preferably 20 to 50% by mass. Within the above range, the more the acrylic polymer B, the better the adhesion to low-polar substrates, and the better the miscibility with low-molecular alcohols, and the lower the viscosity of the aqueous coating composition, the better the coatability. Also, the less the content, the better the film-forming properties of the coating film, the adhesion to polar substrates, and the dispersion stability of the aqueous resin dispersion tend to be.
[0013] The urethane polymer A is preferably a urethane polymer having an average particle size and molecular weight that can be mixed with the (meth)acrylic monomer used in the synthesis of the acrylic polymer B. As the urethane polymer, a commercially available aqueous urethane emulsion may be used as it is. Specifically, Bayhydrol UH2606, Bayhydrol UH650, Bayhydrol UHXP2648 / 1, Bayhydrol UHXP2650, Implanil DLE, Implanil DLC-F, Implanil DLN, Implanil DLN-W50, Implanil DLP-R, Implanil DLS, Implanil DLU, Implanil XP2611, Implanil LP RSC 1380, Implanil LP RSC 1537, Implanil LP RSC 1554, Implanil LP RSC manufactured by Sumika Covestro Urethane Co., Ltd. 3040;Dainippon Ink & Chemicals Co., Ltd.: Hydran HW-301, HW-310, HW-311, HW-312B, HW-333, HW-340, HW-350, HW-375, HW-920, HW-930, HW-940, HW-950, HW-970, AP-10, AP-20, ECOS3000;Sanyo Chemical Industries, Ltd.: Euprene UXA-3005, Chemethylene GA-500;Daiichi Kogyo Seiyaku Co., Ltd. Commercially available products such as Superflex 110, Superflex 150, Superflex 260S, Superflex 210, Superflex 420, and Superflex 500M manufactured by Adeka Corporation; Adeka Bontitor UHX-210 and Adeka Bontitor UHX-280 manufactured by Adeka Corporation; and Takelac W-4000, Takelac W-6010, and Takelac W-6110 manufactured by Mitsui Chemicals, Inc. may also be used.
[0014] The polyol a is an organic compound having at least two hydroxyl groups in one molecule, and various types of polyols can be used. Specific examples of the polyol a include low molecular weight polyols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, trimethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, hexanediol, and cyclohexanedimethanol; and mixtures of at least one of the low molecular weight polyols with ethylene oxide, propylene oxide, or the like. , tetrahydrofuran, or the like; polyester polyols obtained by polycondensing at least one of the above-mentioned low-molecular-weight polyols with a dicarboxylic acid such as adipic acid, sebacic acid, itaconic acid, maleic anhydride, terephthalic acid, isophthalic acid, or the like, polyether polyols such as polyethylene glycol, polypropylene glycol, polycaprolactone polyol, polytetramethylene ether polyol, and polycarbonate polyol; and other polybutadiene polyols, hydrogenated polybutadiene polyols, polyacrylic ester polyols, and the like. These may be used alone or in combination of two or more.
[0015] The polyisocyanate b is an organic compound having at least two isocyanate groups in one molecule, and various polyisocyanates can be used. Specific examples of the polyisocyanate b include ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), dodecamethylene diisocyanate, 1,6,11-undecane triisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2,6-diisocyanatomethyl caproate, bis(2-isocyanatoethyl) fumarate, and biisocyanate. Aliphatic polyisocyanates such as bis(2-isocyanatoethyl)carbonate and 2-isocyanatoethyl-2,6-diisocyanatohexanoate; isophorone diisocyanate (IPDI), 4,4'-dicyclohexylmethane diisocyanate (hydrogenated MDI), cyclohexylene diisocyanate, methylcyclohexylene diisocyanate (hydrogenated TDI), bis(2-isocyanatoethyl)-4-cyclohexene- Alicyclic polyisocyanates such as 1,2-dicarboxylate, 2,5-norbornane diisocyanate, and 2,6-norbornane diisocyanate; 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate (TDI), 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 2,4-diphenylmethane diisocyanate, 4, Examples of the aromatic polyisocyanates include 4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatodiphenylmethane, 1,5-naphthylene diisocyanate, 4,4',4''-triphenylmethane triisocyanate, m-isocyanatophenylsulfonyl isocyanate, and p-isocyanatophenylsulfonyl isocyanate. These may be used alone or in combination of two or more.
[0016] The urethane polymer A can be produced, for example, by reacting the polyol a with the polyisocyanate b in an ether such as dioxane using a catalyst such as dibutyltin dilaurate.
[0017] <Acrylic polymer B> The acrylic polymer B has a structural unit derived from a (meth)acrylic monomer. The polymer B may contain a structural unit derived from a radically polymerizable monomer other than a (meth)acrylic monomer. The radically polymerizable monomer is a monomer having a radically polymerizable group, and examples of the radically polymerizable monomer include a monomer having a radically polymerizable carbon-carbon unsaturated double bond, a radically polymerizable carbon-carbon unsaturated triple bond, a radically ring-opening polymerizable ring, and the like.
[0018] The acrylic polymer B is a component having the function of improving the miscibility with low molecular weight alcohols and imparting adhesion to a low polarity substrate such as polypropylene to the resulting coating film. The acrylic polymer B has a constitutional unit derived from a radical polymerizable monomer c having an alicyclic skeleton, and may have a constitutional unit derived from another vinyl monomer d copolymerizable with the monomer c as necessary. The acrylic polymer B preferably has 5% by mass or more of constitutional units derived from a radical polymerizable monomer having an alicyclic skeleton, more preferably 10% by mass or more, and even more preferably 30% by mass or more. Within the above range, the more constitutional units derived from a radical polymerizable monomer having an alicyclic skeleton, the more the dispersion stability of the aqueous resin dispersion is improved and the resulting coating film tends to be imparted with adhesion to a low polarity substrate. In addition, the more constitutional units derived from a radical polymerizable monomer having an alicyclic skeleton, the more the miscibility of the aqueous resin dispersion with low molecular weight alcohols is improved, and the aqueous coating composition tends to have a low viscosity, improved coatability, and good gloss. Furthermore, the fewer the constituent units derived from the radically polymerizable monomer having an alicyclic skeleton, the better the film-forming properties of the aqueous coating composition, and the more likely it is that the adhesion of the resulting coating film to a polar substrate will be improved.
[0019] Specific examples of the radical polymerizable monomer c having an alicyclic skeleton include cyclohexyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, isobornyl (meth)acrylate, 4-t-butylcyclohexyl (meth)acrylate, etc. Among these, cyclohexyl (meth)acrylate is preferred from the viewpoint of ease of polymerization when producing the polymer B.
[0020] The other vinyl monomer d copolymerizable with the radically polymerizable monomer c having an alicyclic skeleton is a component that adjusts the physical properties and characteristics of the acrylic polymer B. Specific examples of the other vinyl monomer d include alkyl (meth)acrylates having an alkyl group of 1 to 18 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; hydroxyalkyl (meth)acrylates, such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; ethylene glycol di(meth)acrylate; Examples of suitable monomers include glycol di(meth)acrylates such as butylene glycol (meth)acrylate, alkylamino (meth)acrylates such as dimethylaminoethyl (meth)acrylate, monomers having an acid group such as (meth)acrylic acid, vinyl sulfonic acid, styrene sulfonic acid, and neutralized salts thereof, and monomers having a vinyl group such as dimethylaminoethyl (meth)acrylate methyl chloride salt, allyl (meth)acrylate, trimethylolpropane tri(meth)acrylate, glycidyl (meth)acrylate, styrene, vinyl acetate, vinyl propionate, and (meth)acrylonitrile. By using such monomers having an acid group, the adhesion to polar substrates and the dispersion stability of the aqueous resin dispersion can be improved.
[0021] The glass transition temperature (Tg) (unit: ° C.) of the acrylic polymer B means a value calculated by the Fox formula shown in the following formula (1).
[0022]
number
[0023] The abbreviations in formula (1) are as follows. Wi: mass fraction of monomer i Tgi: Tg of the homopolymer of monomer i (℃) For the Tg of a homopolymer, the numerical value described in "Polymer Handbook, 4th Edition, John Wiley & Sons" can be used. For the Tg of a homopolymer not described in the Polymer Handbook, the value actually measured by a differential scanning calorimeter can be used.
[0024] The glass transition temperature of the acrylic polymer B is -60°C or more and less than 5°C, preferably -40°C or more and less than -2°C, more preferably -40°C or more and less than -6°C, and particularly preferably -40°C or more and less than -10°C. Within the above range, the higher the glass transition temperature, the more the blocking resistance tends to improve. In addition, the lower the glass transition temperature, the more the adhesion to a low-polarity substrate tends to improve and the gloss tends to be good. The glass transition temperature of the acrylic polymer B can be adjusted to a low glass transition temperature value by, for example, increasing the ratio of structural units derived from long-chain alkyl (meth)acrylates such as lauryl (meth)acrylate and stearyl (meth)acrylate, and the like, and can be adjusted to a high glass transition temperature value by increasing the ratio of structural units derived from short-chain alkyl (meth)acrylates such as methyl (meth)acrylate and ethyl (meth)acrylate, or (meth)acrylates having a rigid structure such as isobornyl (meth)acrylate. Furthermore, when butyl acrylate and cyclohexyl methacrylate are used as monomers, the glass transition temperature can be made lower by increasing the ratio of structural units derived from butyl acrylate, and the glass transition temperature can be made higher by increasing the ratio of structural units derived from cyclohexyl methacrylate. The SP value of the acrylic polymer B calculated by the fedors' estimation formula from the feed ratio of the raw material monomers is 9.5 to 11.0 (cal / cm 3 ) 1 / 2 is preferable, and 9.7 to 10.1 (cal / cm 3 ) 1 / 2 Within the above range, the larger the SP value, the better the adhesion of the coating film to the polar substrate. Also, the smaller the SP value, the better the miscibility with low molecular weight alcohols, and the lower the viscosity of the aqueous coating composition, the better the coatability.
[0025] An example of a method for producing the aqueous resin dispersion of the present invention containing the urethane polymer A and the acrylic polymer B in the same particle is a method (seed polymerization) in which a radically polymerizable monomer c having an alicyclic skeleton and, as an optional component, another vinyl monomer d copolymerizable with the monomer c are polymerized in the presence of an aqueous medium and the urethane polymer A to produce an aqueous resin dispersion liquid containing the urethane polymer A and the acrylic polymer B in the same particle. The particles contained in the aqueous resin dispersion liquid obtained by seed polymerization may be core-shell particles having a core layer (core) and a shell layer (shell), in which the core layer contains the urethane polymer A and the shell layer contains an acrylic polymer.
[0026] In the polymerization, a conventional radical polymerization initiator may be used as the radical polymerization initiator, and examples of the radical polymerization initiator include azo initiators such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and azobiscyanovaleric acid, persulfate initiators such as sodium persulfate, potassium persulfate, and ammonium persulfate, and organic peroxide initiators such as t-butyl hydroperoxide, dilauroyl peroxide, t-butylperoxy-2-ethylhexanoate, and t-butylperoxypivalate. Redox polymerization initiators in which an organic peroxide initiator or a persulfate initiator is combined with a reducing agent such as ascorbic acid, Rongalite, or a metal sulfite may also be used. The amount of the radical polymerization initiator used is preferably 0.01 to 5% by mass, more preferably 0.05 to 2% by mass, based on the total mass of the (meth)acrylic monomer and the other monomer d. Within the above range, the more the amount of radical polymerization initiator used, the lower the molecular weight of the acrylic polymer B, and the better the wettability to the substrate. Also, the less the amount of radical polymerization initiator used, the higher the molecular weight of the acrylic polymer B, and the less the particle swelling caused by the low molecular weight alcohol, so that the aqueous coating composition has a low viscosity and the coating property tends to be improved. Also, the less the amount of radical polymerization initiator used, the higher the cohesive strength of the coating film tends to be. The molecular weight of the acrylic polymer B can be adjusted, for example, by adding an appropriate amount of a chain transfer agent such as n-dodecyl mercaptan, 1-octanethiol, or 2-ethylhexyl ether thioglycolate during polymerization.
[0027] The polymerization temperature is preferably 10 to 90°C, more preferably 30 to 70°C. Within the above range, the higher the polymerization temperature, the more the polymerization reaction is accelerated and the amount of low molecular weight components can be reduced efficiently. Furthermore, the lower the polymerization temperature, the more the energy required for the polymerization process can be reduced. The polymerization is usually almost completed by maintaining the temperature at about 40 to 90°C for about 30 minutes to 3 hours after the heat generation has ended.
[0028] When an emulsifier is used as necessary during the polymerization, the emulsion can be further stabilized. The amount of the emulsifier used is usually preferably 0.05 to 10% by mass, more preferably 0.1 to 5% by mass, based on the total mass of the monomers used as polymerization raw materials. Within the above range, the larger the amount of emulsifier used, the more the dispersion stability of the dispersion tends to improve. Also, the smaller the amount of emulsifier used, the more the adhesion to low-polarity substrates tends to improve. As the emulsifier, an anionic, cationic, or nonionic surfactant can be used. These may be used alone or in combination of two or more.
[0029] Specific examples of the anionic surfactant include non-reactive surfactants such as potassium oleate, sodium laurate, sodium dodecylbenzenesulfonate, sodium alkanesulfonate, sodium alkylnaphthalenesulfonate, sodium dialkylsulfosuccinate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkyl allyl ether sulfate, polyoxyethylene alkyl phosphate, and polyoxyethylene alkyl allyl phosphate, as well as alkyl allyl sulfosuccinates (e.g., ELEMINOL (registered trademark) JS-2 manufactured by Sanyo Chemical Industries, Ltd., and LATEMUL (registered trademark) S-180A and S-180 manufactured by Kao Corporation), polyoxyethylene alkylpropenyl phenyl ether sulfate ammonium salts (e.g., AQUALON (registered trademark) HS-10, HS-5, BC-10, and BC-5 manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), α Examples of reactive surfactants include -sulfo-ω-(1-(nonylphenoxy)methyl-2-(2-propenyloxy)ethoxy)-poly(oxy-1,2-ethanediyl)ammonium salt (for example, ADEKA REASOAP (registered trademark) SE-10 and SE-1025A manufactured by Asahi Denka Kogyo Co., Ltd.), polyoxyethylene-1-(allyloxymethyl)alkyl ether sulfate ester ammonium salt (for example, AQUALON (registered trademark) KH-10 manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.), α-sulfo-ω-(1-(alkoxy)methyl-2-(2-propenyloxy)ethoxy)-poly(oxy-1,2-ethanediyl)ammonium salt (for example, ADEKA REASOAP (registered trademark) SR-10 and SR-1025 manufactured by ADEKA Corporation), and polyoxyalkylene alkenyl ether sulfate ammonium salt (for example, LATEMURU (registered trademark) PD-104 manufactured by Kao Corporation). Specific examples of the cationic surfactant include non-reactive surfactants such as stearylamine hydrochloride, lauryltrimethylammonium chloride, and trimethyloctadecylammonium chloride.
[0030] Specific examples of the nonionic surfactant include non-reactive surfactants such as polyoxyethylene alkyl ether, polyoxyethylene alkyl allyl ether, polyoxyethylene oxypropyl block polymer, polyethylene glycol fatty acid ester, and polyoxyethylene sorbitan fatty acid ester; and reactive surfactants such as α-hydro-ω-(1-alkoxymethyl-2-(2-propenyloxy)ethoxy)-poly(oxy-1,2-ethanediyl) (manufactured by Asahi Denka Kogyo Co., Ltd.: Adeka Reasoap ER-10, ER-20, ER-30, and ER-40), polyoxyethylene alkyl propenyl phenyl ether (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.: Aqualon RN-20, RN-30, and RN-50), and polyoxyalkyl alkenyl ether (manufactured by Kao Corporation: Latemul PD-420, PD-430, and PD-450).
[0031] The acid value of the aqueous resin dispersion containing the urethane polymer A and the acrylic polymer B in the same particle is preferably 3 to 40 mgKOH / g, more preferably 5 to 20 mgKOH / g. Within the above range, the higher the acid value, the better the dispersion stability of the dispersion, and the lower the acid value, the better the miscibility with low molecular weight alcohols, and the lower the viscosity of the aqueous coating composition, which tends to improve the coatability. The inclusion of the urethane polymer A and the acrylic polymer B in the same particle can be determined by staining an ultrathin section prepared by a general gel embedding method with ruthenium oxide and observing it using a transmission electron microscope.
[0032] The hydrodynamic average particle diameter of the aqueous resin dispersion containing the urethane polymer A and the acrylic polymer B in the same particle is preferably 30 to 150 nm, more preferably 40 to 100 nm. Within the above range, the smaller the hydrodynamic average particle diameter, the better the pigment dispersibility, and the larger the hydrodynamic average particle diameter, the lower the viscosity of the dispersion and the viscosity of the aqueous coating composition, which tends to improve the coatability. The term "hydrodynamic mean particle size" as used herein means the value of the harmonic mean particle size based on scattered light intensity measured at room temperature using a particle size distribution measuring device based on photon correlation method (e.g., Otsuka Electronics Co., Ltd.'s Concentrated System Particle Size Analyzer FPAR-1000) and calculated by cumulant analysis.
[0033] The main solvent of the ink composition containing the aqueous resin dispersion is water, but the ink composition may contain a solvent other than water, such as an alcohol-based solvent, a glycol-based solvent, or a carbitol-based solvent. These may be used alone or in combination of two or more. The content of the solvent other than water is preferably 3 to 60 mass %, more preferably 5 to 50 mass %, based on the total mass of all the solvents. Within the above range, the higher the content of the solvent other than water, the better the film-forming property of the aqueous coating composition and the better the gloss tends to be. Also, the higher the content of the solvent other than water, the better the drying property of the coating film tends to be. Also, the lower the content of the solvent other than water, the lower the viscosity of the aqueous coating composition and the better the coatability tends to be.
[0034] The ink composition containing the aqueous resin dispersion can be produced by blending the aqueous resin dispersion of the present invention with a pigment and the solvent, and may contain an auxiliary as a blending component. Examples of the auxiliary include an acrylic pigment dispersion resin, a defoaming agent such as a silicone resin, a lubricant such as a polyethylene wax, a surfactant, a leveling agent, and a preservative.
[0035] The ink of the present invention containing the aqueous resin dispersion can be produced by mixing a pigment, a resin, and water. Examples of the method for producing the ink include a method having the following varnish production step, a pigment dispersion step, and a product finishing step.
[0036] <Varnish manufacturing process> In the varnish production process, the pigment dispersion resin and the aqueous solution containing the alcohol are mixed together. The mixing may or may not be performed with heating. In order to provide a pigment paste with a viscosity that is easy to handle in the following pigment dispersion step, the concentration of the varnish is preferably 20 to 40% by mass.
[0037] <Pigment dispersion process> In the pigment dispersion process, first, the pigment and the varnish are mixed to produce a premix, and then the obtained premix is kneaded using a dispersing machine. By kneading, the aggregated pigment is dispersed, and a pigment paste in which the pigment dispersion resin is adsorbed on the surface of the pigment is produced. Examples of dispersing machines used in kneading include a bead mill, a sand mill, a ball mill, an attritor, and a roll mill.
[0038] <Product finishing process> In the product finishing step, the pigment paste and the aqueous resin dispersion are mixed to produce an ink composition. In the product finishing step, a diluent containing at least one of water and an organic solvent may be added as necessary to adjust the solid content concentration of the ink. When the ink contains the auxiliary agent, the auxiliary agent can be appropriately blended in the product finishing step, or the auxiliary agent can be blended in a step prior to the product finishing step.
[0039] The ink is suitably used when printing on the surface of a printing medium such as a resin film, a resin molded article, or paper. Examples of the printing method for the ink include gravure printing, offset printing, flexographic printing, inkjet printing, spray coating, roller coating, bar coating, air knife coating, casting, brush coating, and dipping. The drying conditions after forming the ink coating film may be appropriately selected depending on the printing method, etc. For example, in the case of gravure printing on a resin film, drying is preferably performed at a temperature range of 20 to 60° C. for 10 seconds to 10 hours. EXAMPLES
[0040] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited thereto. In the examples and comparative examples, "parts" and "%" mean "parts by mass" and "% by mass", respectively.
[0041] Synthesis Example 1: Preparation of an aqueous resin dispersion containing urethane polymer A and acrylic polymer B in the same particle A flask equipped with a stirrer, a reflux condenser, a temperature control device, and a dropping pump was charged with 285.7 parts (solids content 100.0 parts) of anionic water-based urethane resin Bayhydrol UH2648 / 1 (manufactured by Sumika Covestro Urethane Co., Ltd., solids content 35.0%) as a dispersion liquid with a solids concentration of 35.0% as urethane polymer A, 247 parts of deionized water, and (meth)acrylic monomers consisting of 79.0 parts of cyclohexyl acrylate (hereinafter abbreviated as CHA) and 21.0 parts of butyl acrylate (hereinafter abbreviated as BA), and the temperature of the flask was raised to 40°C. Thereafter, 0.02 parts of t-butyl hydroperoxide aqueous solution (manufactured by Arkema Yoshitomi Co., Ltd., trade name: Luperox TBH68X, solid content 68%) as a polymerization initiator, 0.0002 parts of ferrous sulfate as a reducing agent, 0.00027 parts of ethylenediaminetetraacetic acid (EDTA), 0.082 parts of sodium isoascorbate monohydrate, and 4 parts of deionized water were added. Subsequently, after confirming the polymerization heat of 0.5 ° C., 0.03 parts of t-butyl hydroperoxide aqueous solution and 20 parts of deionized water were dropped for 15 minutes. After confirming the peak top temperature due to the polymerization heat, the internal temperature of the flask was raised to 60 ° C., and 0.05 parts of t-butyl hydroperoxide aqueous solution, 0.082 parts of sodium isoascorbate monohydrate, and 4 parts of deionized water were added in two separate batches. The reaction solution was then cooled to obtain an aqueous resin dispersion with a solid content of 30% containing the urethane polymer A and the acrylic polymer B in the same particle. The synthesis results of the obtained aqueous resin dispersion and the morphology of the resin are shown in Table 1.
[0042] <Synthesis Examples 2 to 9> Preparation of aqueous resin dispersions containing urethane polymer A and acrylic polymer B in the same particle An aqueous resin dispersion having a solid content concentration of 30% and containing urethane polymer A and acrylic polymer B in the same particle was obtained by carrying out the same operation as in Synthesis Example 1, except that the monomer composition ratio was set as shown in Table 1. The synthesis results of the obtained aqueous resin dispersion and the morphology of the resin are shown in Table 1.
[0043] Synthesis Example 10: Preparation of an aqueous resin dispersion mixture of urethane polymer A and acrylic polymer B not containing urethane polymer A and acrylic polymer B in the same particle In a flask equipped with a stirrer, a reflux condenser, a temperature control device and a dropping pump, 180 parts of deionized water and 3.8 parts (0.95 parts of solids) of ADEKA REASOAP SR-1025 (manufactured by ADEKA Corporation, solids content 25.0%) as a dispersion liquid with a solids concentration of 25.0% were charged, and the internal temperature of the flask was raised to 80°C. 0.5 hours after the temperature stabilized, a pre-emulsion liquid in which 2.5 parts of cyclohexyl methacrylate (hereinafter abbreviated as CHMA), 2.5 parts of BA, 2.0 parts of deionized water and 0.19 parts of ADEKA REASOAP SR-1025 were emulsified and dispersed in advance, and 1.0 part of deionized water were charged and stirred for 0.5 hours. Then, an aqueous polymerization initiator solution in which 0.3 parts of ammonium persulfate was dissolved in 3.0 parts of deionized water as a polymerization initiator was added. After the peak top temperature due to the polymerization heat was confirmed and the internal temperature returned to 80°C, a pre-emulsion liquid in which 47 parts of CHMA, 47 parts of BA, 38 parts of deionized water, and 3.6 parts of Adeka Reasoap SR-1025 were previously emulsified and dispersed was added dropwise over 2 hours and 30 minutes. The internal temperature was maintained at 80°C during the dropwise addition. After stirring was continued for 1 hour and 30 minutes from the end of the dropwise addition while maintaining the internal temperature at 80°C, the reaction liquid was cooled to obtain an aqueous resin dispersion of acrylic polymer B with a solid content concentration of 30%. As an aqueous resin dispersion of urethane polymer A, equal amounts of Bayhydrol UH2648 / 1 and the aqueous resin dispersion of acrylic polymer B were mixed to obtain an aqueous resin dispersion mixture of urethane polymer A and acrylic polymer B in which urethane polymer A and acrylic polymer B were not contained in the same particle. The synthesis results of the obtained aqueous resin dispersion mixture and the form of the resin are shown in Table 1.
[0044] <Preparation of Dispersant> In a polymerization apparatus equipped with a stirrer, a cooling tube, and a thermometer, 900 parts of deionized water, 60 parts of 2-sulfoethyl sodium methacrylate, 10 parts of potassium methacrylate, and 12 parts of methyl methacrylate (hereinafter, abbreviated as MMA) were put and stirred, and the temperature was raised to 50°C while replacing the atmosphere in the polymerization apparatus with nitrogen. Next, 0.08 parts of 2,2'-azobis(2-methylpropionamidine) dihydrochloride was added as a polymerization initiator, and the temperature was raised to 60°C. After the temperature was raised, MMA was continuously dropped at a rate of 0.24 parts / min for 75 minutes using a dropping pump. The total amount of MMA added by the above dropping was 18 parts. After the dropwise addition was completed, the reaction solution was kept at 60°C for 6 hours, and then cooled to room temperature to obtain a dispersant with a solid content concentration of 10% as a transparent aqueous solution.
[0045] <Production of pigment dispersion resin> In a polymerization apparatus equipped with a stirrer, a cooling tube, and a thermometer, 145 parts of deionized water, 0.1 part of sodium sulfate, and 0.25 parts of the dispersant (solid concentration 10%) were placed and stirred to prepare a homogeneous aqueous solution. Next, 13 parts of MMA, 10 parts of styrene (hereinafter abbreviated as St), 67 parts of n-butyl methacrylate (hereinafter abbreviated as n-BMA), and 10 parts of methacrylic acid (hereinafter abbreviated as MAA) were added and stirring was started again, and 0.5 parts of 2,2-dimethyl-2,2-diazenediyldibutanenitrile (hereinafter abbreviated as AMBN) and 1.9 parts of n-dodecyl mercaptan (hereinafter abbreviated as n-DM), 1.9 parts of 1-octanethiol (hereinafter abbreviated as n-OM), and 1.9 parts of thioglycolic acid 2-ethylhexyl ether (hereinafter abbreviated as OTG) were added and heated to 80 ° C., and the reaction was carried out for 2 hours while maintaining the reaction temperature at 80 to 85 ° C., and then the temperature was raised to 95 ° C. and maintained for 1 hour to terminate the reaction. The resulting pigment dispersion resin had a molecular weight of 8,000 and an acid value of 61 mg KOH / g.
[0046] <Dissolving and neutralizing pigment dispersion resin> In a 200 ml flask equipped with a stirrer and a thermometer, 90 g of the pigment dispersion resin, 81.3 g of isopropyl alcohol (hereinafter abbreviated as IPA), and 120 g of deionized water were added, stirring was started, and 8.7 g of dimethylaminoethanol (hereinafter abbreviated as DMAE) was gradually added. After that, the temperature was maintained at room temperature (25°C) for 2 hours to complete dissolution, and the pigment dispersion resin was neutralized with dimethylaminoethanol to obtain a pigment dispersion resin varnish.
[0047] Example 1 45 g of the pigment dispersion resin varnish was taken, and 9.0 g of a pigment dispersant TEGO740 (manufactured by Evonik), 157.5 g of a pigment (titanium oxide manufactured by Ishihara Sangyo Kaisha, Ltd., product name: CR-90), 36.0 g of deionized water, 67.5 g of IPA, and 60.0 g of glass beads were mixed and stirred in this order to obtain a premix. The premix was kneaded for 3 hours using a rocking shaker to obtain a pigment paste. The degree of dispersion of the pigment paste was evaluated using a particle cage. Then, 20 g of the pigment paste was taken, and 8.6 g of the aqueous resin dispersion obtained in Synthesis Example 1 was added, and the mixture was thoroughly stirred to prepare an ink. The ink was diluted with 10.3 g of IPA and 12.6 g of pure water. The diluted ink was used to print on the corona-treated surfaces of a biaxially oriented polypropylene (hereinafter abbreviated as OPP) film (manufactured by Toyobo Co., Ltd., product name: P-2108) and a polyethylene terephthalate (hereinafter abbreviated as PET) film (manufactured by Futamura Chemical Co., Ltd., product name: FE2001) using a gravure printing machine (manufactured by RK in the UK, product name: GP-100). An ink coating film was formed to a thickness of 1 to 2 μm. The ink coating film was dried under drying conditions of 25° C. for 1 day. The smoothness of the ink coating film after drying was evaluated. The evaluation results of the ink viscosity, the coating film smoothness, gloss, and adhesion to various substrates are shown in Table 2. The evaluation method is as follows.
[0048] [Ink Viscosity] The viscosity of the formulated ink was measured at 23° C. using a Zahn Cup No. 3 (manufactured by Tester Sangyo Co., Ltd.) and the ink viscosity was evaluated according to the following evaluation criteria. (Evaluation Criteria) ◯: The Zahn cup passing time is less than 10 seconds, and the viscosity is low and the coating property is excellent. ×: The Zahn cup passing time was 10.0 seconds or more, and the viscosity was high and the applicability was poor.
[0049] [Gloss] The gloss (60°) of the ink coating having a thickness of 1 to 2 μm after drying was measured using a variable angle gloss meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name: GLOSS METER VG7000) and the gloss was evaluated according to the following evaluation criteria. (Evaluation Criteria) ⊚: Gloss value is 11.5 or more. ◯: Gloss value is 11.0 or more and less than 11.5. Δ: Gloss value is higher than 10.5 and less than 11.0. ×: The gloss value is 10.5 or less.
[0050] [Adhesion to substrate] After drying, cellophane tape (manufactured by Nichiban Co., Ltd., product name: CT405AP-12) was applied to the ink coating film having a thickness of 1 to 2 μm, and a peeling test was performed in the vertical direction. The adhesion to the substrate was evaluated based on the percentage of the area where the ink had peeled off, according to the following evaluation criteria. (Evaluation Criteria) ⊚: The ink remaining on the substrate after the peeling test was 80% or more, and the adhesion was excellent. ◯: The ink remaining on the substrate after the peel test was 25% or more and less than 80%, and the adhesion was good. Δ: The ink remaining on the substrate after the peeling test was 15% or more and less than 25%, which was at a practical level. ×: The rate of ink remaining on the substrate after the peeling test was less than 15%, not satisfying the practical level.
[0051] [Examples 2 to 5 and Comparative Examples 1 to 5] Inks were produced in the same manner as in Example 1, except that the aqueous resin dispersions of Synthesis Examples 2 to 10 were used instead of the aqueous resin dispersion of Synthesis Example 1, and evaluated for the same evaluation items as in Example 1. The evaluation results are shown in Table 2.
[0052] [Table 1]
[0053] [Table 2]
[0054] The abbreviations in Tables 1 and 2 have the following meanings: CHMA: Cyclohexyl (meth)acrylate CHA: Cyclohexyl acrylate IBXA: Isobornyl acrylate BA: n-butyl acrylate St: styrene
[0055] In Examples 1 to 5, in which the ink of the present invention containing the aqueous resin dispersion of the present invention was used, the ink had a low viscosity and was excellent in coatability, and the ink coating film after drying had excellent smoothness and gloss, and also had good adhesion to OPP substrates and PET substrates. In Comparative Examples 1 and 4, in which an acrylic polymer having a glass transition temperature outside the range specified in the present application was used, the gloss of the ink coating after drying was poor. On the other hand, in Comparative Examples 2 and 3, in which an acrylic polymer not having a constituent unit derived from a radically polymerizable monomer having an alicyclic skeleton was used, either the adhesion of the ink coating film to the substrate or the gloss after drying was poor. In Comparative Example 5, in which an aqueous resin dispersion not containing urethane polymer A and acrylic polymer B in the same particle was used, the ink had a high viscosity and poor coatability. [Industrial Applicability]
[0056] The aqueous resin dispersion of the present invention and the ink containing the dispersion have low viscosity and excellent coatability, and can give coating films having good adhesion to various plastic film substrates and good gloss. Therefore, they can be suitably used as raw materials for aqueous coating compositions such as aqueous inks, and are therefore extremely important from an industrial perspective.
Claims
1. An aqueous resin dispersion containing, in the same particle, a urethane polymer A and an acrylic polymer B obtained by seed polymerization of a radically polymerizable monomer having an alicyclic skeleton, wherein the content of the acrylic polymer B relative to the total mass of the urethane polymer A and the acrylic polymer B is 10 to 80 mass %, the acrylic polymer B has a constitutional unit derived from a radically polymerizable monomer having an alicyclic skeleton and a constitutional unit derived from an alkyl (meth)acrylate having an alkyl group having 1 to 18 carbon atoms, the acrylic polymer B has a constitutional unit derived from a radically polymerizable monomer having an alicyclic skeleton of 10 mass % or more relative to the total mass of the constitutional units constituting the acrylic polymer B, and the glass transition temperature of the acrylic polymer B is -60°C or more and less than 5°C.
2. The aqueous resin dispersion according to claim 1, wherein the acrylic polymer B has a glass transition temperature of -40°C or higher and -2°C or lower.
3. The aqueous resin dispersion according to any one of claims 1 to 2, wherein the acrylic polymer B has a glass transition temperature of -40°C or more and -6°C or less.
4. The aqueous resin dispersion according to any one of claims 1 to 3, wherein the aqueous resin dispersion has a hydrodynamic average particle size of 120 nm or less as measured by a dynamic light scattering method.
5. The aqueous resin dispersion according to any one of claims 1 to 4, wherein the solid content of the aqueous resin dispersion is 35 mass % or more based on the total mass of the aqueous resin dispersion.
6. The method for producing the aqueous resin dispersion according to any one of claims 1 to 5, wherein the acrylic polymer B is produced by polymerization using 0.35 mass% or less of a radical polymerization initiator based on a total amount of radically polymerizable monomers for constituting the acrylic polymer B.
7. The method for producing an aqueous resin dispersion according to any one of claims 1 to 5, wherein the particles are produced by seed polymerization of a radical polymerizable monomer for constituting the acrylic polymer B using the urethane polymer A as a seed.
8. An ink comprising the aqueous resin dispersion according to any one of claims 1 to 5.
Citation Information
Patent Citations
Urethane resin-based curable resin composition and its manufacturing method
JP2002212415A
Aqueous resin composition and aqueous coating material
JP2003342313A
Method for producing urethane-acrylic inner particle mixture aqueous dispersion
JP2005120304A
Polyurethane-vinyl polymer composite resin water-based dispersion
JP2008111037A
Acrylic-urethane block copolymer aqueous emulsion, method for producing the same, and aqueous coating material
JP2009057451A